China’s cross-border maritime data flow governance: progress, challenges, and prospects - Yu, Minna; Wang, Liu (Frontiers in Marine Science, 2025)
The rise of the big data strategy and the concept of new productive forces in China amplifies the significance of cross-border maritime data flow in driving the growth of the shipping economy. While China has made notable progress in facilitating and regulating cross-border maritime data flow through legislative and policy initiatives, the existing framework remains general and fragmented, falling short of addressing the specific and complex requirements of maritime data practices. Using normative and comparative analysis, this paper systematically examines the legal and policy landscape surrounding cross-border maritime data transfer in China, including laws, departmental regulations, and industry standards. It identifies two critical challenges: the conflict between promoting cross-border maritime data transfer and safeguarding national security interests, and the shortcomings in the maritime data classification and grading system. Finally, this paper proposes a multi-faceted approach to address these issues, emphasizing technological innovation, fostering international cooperation to establish unified technical standards, and advancing the legalization of the “national security” concept. It further advocates for building international consensus on defining “national security” within the context of maritime data governance, aiming to balance the facilitation of cross-border data flow with the protection of national security interests.